Immersed symmetries in the making Galapa's torito mask (2020)
The research issue consisted in the need to recognize other ways of mathematic knowledge, specifically geometric, created by the artisans from Galapa, Colombia, in the Torito mask manufacture. For this reason, the target was to identify the symmetries used in the making of the masks analyzed. The theoretical framework will have as reference the Ethno-mathematics program, together with the theoretical assumptions raised by Bishop and taking into account colour and shape. The methodology applied was qualitative, with an ethnographic method. The results show the use of unsystematic measurements implemented by craftsmen from the first to the last phase of the Torito mask making, standing out the symmetries used and their potential contribution to mathematics education, especially to geometry.